Measures to overcome the barriers that hinder the adoption of energy-efficient technologies in the Brazilian building segment - Cristino, Talita Mariane [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The imminent global energy crisis combined with an uncertain climate future highlights the urgency to mitigate undesirable concerns about excessive energy consumption and its environmental impacts. This scenario has led to the development of several actions to reduce global energy consumption. For decades, these actions were directed towards to the industrial segment, since it was the greatest energy consumer in society. However, as time went by, residential, commercial, and public buildings have gained prominence, since they have become responsible for one-third of global final energy consumed and for 15% of greenhouse gas emissions. This scenario is not quite different in Brazil. The energy consumption of this segment has also been growing consistently over the last decades. Therefore, it is important to find ways to reduce the energy consumption of this segment without affecting the comfort and well-being of society. Energy efficiency is the key to solving this issue, in other words, the adoption of energy-efficient (EE) technologies is the best way to deal with this challenge. However, despite the benefits and positive projections linked to such technologies, they have not been widely adopted in buildings, due to the existence of barriers that hinder their adoption. In the literature, there are many publications aimed to identify such barriers. But, just a small portion of them focus on measures to overcome them. And none is dedicated to the Brazilian reality. Therefore, this research aimed to fill this gap. Firstly, it was important to develop a conceptual framework that provides a comprehensive understanding of the barriers that hinder the adoption of EE technologies. Thus, as a result, this framework enabled the delineation of the process of EE technology adoption, highlighting its necessary steps and the stakeholders involved. Notably, the adoption process was subdivided into four stages (Motivation, Information, Planning/Execution, and Results) shaped by both the government and the market. This result still allowed for a meticulous mapping of the barriers specific to the Brazilian context within the adoption process, thus identifying the process stages at which each barrier may emerge. Subsequently, it was possible to study the interrelationships between the barriers that emerge at each stage of the adoption process. This analysis was performed using the ISM (Interpretative Structural Modelling) technique. As a result, it was possible to construct hierarchical structures among the barriers that emerge in each stage of the adoption process, enabling the identification of the critical ones: lack of knowledge on energy efficiency by regulators and legislators (Government Support); lack of financial incentives (“Motivation” phase); lack of demonstration projects (“Information” phase); lack of technical competence and lack of adequate technologies (“Planning/Execution” phase); and lack of good marketing strategies (Market Expansion). From the identification of these critical barriers, it was possible to propose measures to overcome them. Initially, a literature review was conducted to identify such measures. Subsequently, these measures were proposed specifically for the Brazilian context. And although this research had suggested measures to overcome the critical barriers, it was also important to present additional suggestions to overcome the remaining barriers that hinder the adoption of EE technologies in the Brazilian building segment. This strategy ensures that not only the critical barriers are addressed, but also the less prominent ones, thereby facilitating a more effective transition to energy-efficient practices across the entire segment. By proposing measures to overcome barriers to the adoption of EE technologies in the building segment, this research contributes significantly to enhancing the efficiency and sustainability of Brazilian buildings. Additionally, it stimulates economic growth and enhances the country’s competitiveness regarding energy issues in the building segment. Thus, the suggested measures not only address immediate challenges but also pave the way for long-term benefits and progress in the Brazilian building segment.

A iminente crise energética global, combinada com um futuro climático incerto, destaca a urgência de mitigar preocupações indesejáveis atreladas ao consumo excessivo de energia e seus impactos ambientais. Este cenário tem levado ao desenvolvimento de diversas ações para reduzir o consumo global de energia. Durante décadas, essas ações foram direcionadas ao segmento industrial, já que é o maior consumidor de energia. Porém, com o passar do tempo, os edifícios residenciais, comerciais e públicos ganharam destaque, uma vez que se tornaram responsáveis por um terço do consumo global de energia e por 15% das emissões totais de gases de efeito estufa. Esse cenário não é muito diferente no Brasil. O consumo de energia deste segmento também tem crescido de forma consistente nas últimas décadas no país. Portanto, é importante encontrar um caminho para reduzir o consumo de energia deste segmento sem afetar o conforto e o bem-estar da sociedade. A eficiência energética é a chave para resolver esta questão, ou seja, a adoção de tecnologias energeticamente eficientes (EE) é a melhor forma de lidar com este desafio. No entanto, apesar dos benefícios e das projeções positivas atreladas a tais tecnologias, elas não têm sido amplamente adotadas, devido à existência de barreiras que dificultam a sua adoção. Na literatura, existem diversas publicações destinadas a identificar tais barreiras. Mas, apenas uma pequena parte delas se concentra em medidas para superar-lás. E nenhuma é dedicada à realidade brasileira. Portanto, esta pesquisa teve como objetivo preencher essa lacuna. Primeiramente, foi importante desenvolver uma estrutura conceitual que proporcionasse uma compreensão abrangente das barreiras que dificultam a adoção de tecnologias EE. Assim, como resultado, foi possível delinear o processo de adoção de tecnologias EE, destacando suas etapas necessárias e os principais envolvidos. Notavelmente, o processo de adoção foi subdividido em quatro etapas (Motivação, Informação, Planejamento/Execução e Resultados) moldadas tanto pelo governo quanto pelo mercado. Esse resultado ainda permitiu um mapeamento meticuloso das barreiras específicas do contexto brasileiro dentro do processo de adoção, identificando assim as barreiras que podem surgir em cada uma das etapas do processo de adoção das tecnologias EE. Posteriormente, as interrelações entre essas barreiras foram analisadas por meio da aplicação da técnica conhecida como Modelagem Estrutural Interpretativa. Como resultado, estruturas hierárquicas das barreiras que podem surgir em cada etapa do processo de adoção foram construídas, permitindo assim identificar cinco barreiras críticas dentro desse processo, que são: falta de conhecimento sobre eficiência energética por parte dos reguladores e legisladores (Apoio Governamental); falta de incentivos financeiros (Fase de “Motivação”); falta de projetos de demonstração (Fase de “Informação”); falta de competência técnica e falta de tecnologias adequadas (Fase de “Planejamento/Execução); e falta de boas estratégias de marketing (Expansão de Mercado). A partir dessa identificação das barreiras críticas foi possível então propor medidas para superá-las. Inicialmente, foi realizada uma revisão de literatura para identificar tais medidas. Posteriormente, essas medidas foram propostas especificamente para o contexto brasileiro. E embora esta pesquisa tenha em um primeiro momento sugerido medidas para superar as barreiras críticas, também foi importante apresentar sugestões adicionais para superar as barreiras restantes que dificultam a adoção de tecnologias EE no segmento de edificações brasileiro. Esta estratégia garante que não só as barreiras mais críticas sejam abordadas, mas também as menos proeminentes, facilitando assim uma transição mais suave e eficaz para práticas de eficiência energética em todo o segmento. Ao propor medidas para superar barreiras à adoção de tecnologias de EE, esta pesquisa contribui significativamente para melhorar a eficiência e a sustentabilidade das edificações no Brasil. Além disso, pode estimular o crescimento econômico e aumenta a competitividade do país em questões energéticas nesse segmento. Assim, as medidas sugeridas não apenas abordam desafios imediatos, mas também podem abrir caminho para benefícios e progresso a longo prazo no setor de edificações brasileiro.
Medidas para superar as barreiras que dificultam a adoção de tecnologias energeticamente eficientes no segmento de edificações do Brasil
Keywords: energy efficiency; building energy efficiency; energy-efficient technologies; barriers; obstacles; overcoming measures; Recursos energéticos; Energia elétrica - Consumo; Construção civil